The Teacher Training Process by Writing the Internship Report - Fabiano-Campos, Sulemi (2020)
In this paper, our objective is to carry out an analysis on how undergraduate language interns mobilize the other’s speech to theoretically base the writing of the internship report. The discussion that we propose comes from the conception that the report is a statement produced as a responsive activity in the training process of future mother tongue teachers in the ways in which the interns understand theoretical points of view and how they relate to the reality observed in the classroom. For the proposed analysis, we support the conception of Bakhtin/Volóchinov (2006) about language as a dialogical activity and about the other’s speech in the production of statements. Our analysis objects are reports produced in different stages of the curricular internship, different writings, and space-times that help us to think about the displacements of students by mobilizing the foreign word for the construction and real comment on the meanings it carries.